How do you feel today? Nurturing emotional awareness among students in online learning. Issue 3 (4th May 2022) - De Leon-Pineda, Josephine Luz
ABSTRACT: Integrating strategy in education to improve the well-being of the students is an undisputable responsibility of teachers. This study assessed the perceptions of the students on the 'How do you feel today-strategy' used by the teacher in her instruction as a way to promote emotional awareness among students and further utilized the information in strategizing online instructions. Mixed-method action research was utilized in this study. The action was implemented in one intact class and twenty-eight preservice teachers' participants volunteered to answer the questionnaire and structured interview questions. The strategy used by the teacher gained positive perceptions from the participants and revealed that it highlighted their emotional awareness. The sense of belonging and a way of validation and reflection of emotions were also determined in the inclusion of the strategy in the instruction. The strategy was also found to bridge the gap of connection between students in the online learning setting and brought positivity in the classroom. The use of this strategy is recommended to be used in other classroom with conscious effort of determining student's characteristics.